The ownership structure of European blue chips: is there a convergence in corporate ownership? - Bresolini Eibenstein, P. (2016)
The two main models of corporate governance originated in the second part of the 20th century: the shareholder model, in the Anglo-Saxon world, and the stakeholder model, in Continental Europe. They are respectively mainly characterized by widespread and concentrated ownership and, consequently, by different agency problems. However, with the phenomenon of globalisation, the increased importance of financial markets and the international success of Anglo-American multinational firms, a debate has arisen as to whether there exists a convergence towards the shareholder oriented model. This research aims to explore this controversy by focusing the analysis on the ownership structure of the blue chip firms in the main stock indexes of Germany, France, Italy, Spain and the UK. The research concludes that a convergence in corporate governance structure towards the shareholder model seems to exist in almost all of those countries.